2020
DOI: 10.1097/md.0000000000020600
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width-to-lymphocyte ratio

Abstract: To evaluate the diagnostic power of red cell distribution width-to-lymphocyte ratio (RLR) for HBV-related liver cirrhosis via a retrospective cohort study. Seven hundred fifty healthy controls, 327 chronic hepatitis B (CHB) patients, and 410 patients with HBV-related liver cirrhosis (HBV-LC) were enrolled in this study. RLR, lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR), red cell distribution width (RDW), AST to platelet ratio index (APRI), and fibrosis index based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…It has been noted that viral load can have a significant effect on RDW when ALT levels are more than 2 times higher than in the normal group (14). High RDW is positively associated with the severity of CHB disease and may be a determining factor in the follow-up of patients with liver cirrhosis (11)(12)(13). Although the increase in ALT levels in this study altered significantly, there was no two-fold difference compared to the control group.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It has been noted that viral load can have a significant effect on RDW when ALT levels are more than 2 times higher than in the normal group (14). High RDW is positively associated with the severity of CHB disease and may be a determining factor in the follow-up of patients with liver cirrhosis (11)(12)(13). Although the increase in ALT levels in this study altered significantly, there was no two-fold difference compared to the control group.…”
Section: Discussioncontrasting
confidence: 55%
“…Atay et al found an increase in NLR rates in the CHB group compared to the controls and in the advanced fibrosis group compared to the mild fibrosis group (15). However, in some recent studies, PLT values were found to be higher in CHBs without cirrhosis and liver failure, and lower NLR values compared to controls (13,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Meanwhile, RDW-CV to platelet ratio could predict fibrosis in patients with chronic hepatitis C, with an AUC of 0.65 [24]. And the RDW-CV to lymphocyte ratio could predict the incidence of CHB liver cirrhosis [25]. Previous study had found that the alcoholic cirrhosis group had a higher level of MCV value compared with alcoholic fatty liver or mild alcoholic hepatitis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between the lymphocyte ratio and EVs has not been reported, previous studies have demonstrated that the lymphocyte count or ratio is associated with HBV-related cirrhosis. Compared with healthy controls, both the lymphocyte count and lymphocyte/monocyte ratio decreased significantly (Zhang et al, 2015;Zhao et al, 2017;Zhang et al, 2020), and the neutrophil/lymphocyte ratio was markedly elevated (Zhao et al, 2017;Zhang et al, 2020). This may be a consequence of chronic systemic inflammation, immune dysfunction, and T-cell exhaustion due to chronic HBV infection (Lombardo et al, 1995;Ye et al, 2015;Kalra et al, 2017).…”
Section: Discussionmentioning
confidence: 96%